2014
DOI: 10.1002/hrm.21593
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Systems and Ethical Climates: A Resource‐Based Perspective

Abstract: We know very little about how ethical climates are built and the potential role of a firm's HR system in facilitating the development of this resource. The resource‐based view (RBV) of the firm suggests that human resource systems directly influence a firm's performance through the development of resources that are deeply woven in a firm's history and culture. How this occurs though has not been thoroughly considered in the research literature. Drawing on the theoretical insights from the resource‐based view o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 118 publications
2
54
0
Order By: Relevance
“…In related argument, training and development can be regarded as internal factor that can create competitive advantage and improve performance. In this regards, this study empirically investigate the effects of ethical climate (EC) as mediating factor among the two variables (training and development and OP) as suggested by previous studies (Arulrajah, 2015;Manroop, Singh, & Ezzedeen, 2014) and also confirmed the argument of RBV, which stated that human resource system can leads to competitive advantage through resources that are indirectly within the organizational circle like ethics (Barney, 2001;Reed & DeFillippi, 1990;Wright & McMahan, 1992). The variable EC had been discussed earlier in the literature by Victor and Cullen (1987;1988).…”
Section: Problem Statementsupporting
confidence: 66%
See 1 more Smart Citation
“…In related argument, training and development can be regarded as internal factor that can create competitive advantage and improve performance. In this regards, this study empirically investigate the effects of ethical climate (EC) as mediating factor among the two variables (training and development and OP) as suggested by previous studies (Arulrajah, 2015;Manroop, Singh, & Ezzedeen, 2014) and also confirmed the argument of RBV, which stated that human resource system can leads to competitive advantage through resources that are indirectly within the organizational circle like ethics (Barney, 2001;Reed & DeFillippi, 1990;Wright & McMahan, 1992). The variable EC had been discussed earlier in the literature by Victor and Cullen (1987;1988).…”
Section: Problem Statementsupporting
confidence: 66%
“…Similarly, the hypothesis on the link between training and development and ethical climate is found significant and supported in this study. The finding was backed up the argument of some previous literature (Arulrajah, 2015;Manroop et al, 2014), the ability of organization to properly trained employees can effect ethical behaviour of personnel within the organization, such ethical behaviour usually depends on the effective functions of the system itself (Foote, 2001) In related development, the role of training and development in promoting EC as well as ethical (Caldwell et al, 2011). Hence, Nigerian PESA needs to be more concern in training of employees to promote organizational ethical system, in return achieve organizational performance.…”
Section: Resultsmentioning
confidence: 90%
“…Based on the above stated justification the researcher intended to employ HRM practices as Independent variables. While on the EC as the moderating variable, previous studies found EC as a strong predictor of organizational performance (Hijal-Moghrabi et al, 2015;Manroop et al, 2014), others prior studies tested EC as moderator on the relationship between job satisfaction and organizational commitment in Asian context (Zehir et al, 2012), African context (Nafei, 2015) result of the previous studies explained positive moderating effect. Based on the above empirical evidences, a proposed research framework for this study illustrating the moderating effect of EC on the relationship between HRM practices and organizational performance is depicted in Figure 1.…”
Section: Proposed Conceptual Modelmentioning
confidence: 93%
“…Therefore, employees can perform through effective utilization of internal resources base on HRM practices. Similarly, In the opinion of Manroop et al (2014) In RBV perspective, EC has been linked to add value to HRM practices and organizational performance in terms of playing a vital role to attain organizational success. EC Emphasizes on having strategic value for organization and how human resource systems may help that value to attain result.…”
Section: Underpinning Theorymentioning
confidence: 99%
See 1 more Smart Citation